Total flavonoids of Selaginella tamariscina (P. Beauv.) Spring ameliorates diabetes-induced acute lung injury via activating Nrf2/ HO-1 - Lina Chen; Guosu Xiao; Zhou Yu; Niwen Huang; Yiju Cheng (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): This investigation explored the mechanism by which the total flavonoids of Selaginella tamariscina (P.Beauv.) Spring (TFST) mitigate oxidative stress through the activation of the heme oxygenase-1 (HO-1) signaling pathway mediated by nuclear factor erythroid 2-related factor 2 (Nrf2), thereby ameliorating acute lung injury (ALI) induced by diabetes. Materials and Methods: Male mice weighing 20–25 grams were divided into four groups: a control group, a diabetic group, a diabetic group treated with TFST, and a diabetic group treated with TFST and ML385. Various biological specimens were collected for analysis, including bronchoalveolar lavage fluid (BALF), blood, and tissue samples. These were subjected to a range of assessments covering hematological and BALF parameters tumor necrosis factor-alpha (TNF-α), interleukin-6 [IL-6]), biochemical markers (malondialdehyde [MDA], superoxide dismutase [SOD], glutathione peroxidase [GSH], Nrf2, and HO-1 levels), along with histopathological evaluations.Results: Pre-treatment with TFST demonstrated a significant decrease in pulmonary tissue damage, evidenced by decreased wet-to-dry (W/D) lung ratios (P<0.001), reduced lung injury scores (P<0.0001), and lower levels of TNF-α, IL-6 (P<0.0001), as well as oxidative stress markers like MDA (P<0.05). Moreover, there was an elevation in the activity of anti-oxidative enzymes, specifically SOD and GSH (P<0.05), coupled with an enhanced expression of Nrf2 and HO-1 in the diabetic group (P<0.01). Conclusion: The study findings demonstrate that TFST can suppress oxidative stress by modulating the Nrf2 pathway and up-regulating HO-1 activity, thereby ameliorating diabetes-induced acute lung injury.